The relationship between non-permanent migration and non-communicable chronic disease outcomes for cancer, heart disease and diabetes - a systematic review - Karen H. Wang; Zoé M. Hendrickson; Cynthia A. Brandt; Marcella Nunez-Smith (BMC, 2019)
Abstract Background The relationship between migration and health has primarily focused on permanent migrants, although non-permanent migrants comprise a large proportion of global migrants. Non-permanent migrants may have distinct needs that affect their health outcomes. This systematic review 1) examined the evidence concerning whether non-permanent migrants have different health outcomes than other population groups for non-communicable chronic diseases (NCDs) and 2) sought to describe how non-permanent migration is defined and measured. Methods For this systematic review, we developed a comprehensive search string for terms about non-permanent migration and disease and screening rates for three NCDs (cancer, heart disease, and diabetes) and searched thirteen electronic databases using the search string. Authors reviewed and evaluated articles for full-text review; hand-searched specific journals and grey literature; and scanned reference lists of relevant studies. Authors extracted and assessed data based on standard reporting for epidemiologic studies. Results We identified twelve peer-reviewed articles that examined NCD outcomes for non-permanent migrants as compared to other populations. Some studies showed worse or no significant differences in the NCD outcomes for non-permanent migrants compared to other groups. The articles reflected substantial diversity that exists among non-permanent migrants, which ranged from economic migrants to nomadic populations. Conclusion Non-permanent migrants varied in their NCD outcomes as compared to other groups. Our included studies were heterogenous in their study designs and their definitions and measurement of non-permanent migration, which limited the ability to make conclusive statements about the health of the populations as compared to other populations. More standardization is needed in research to better understand the diversity in these populations and quantify differences in risk factors and disease rates between non-permanent migrants and other groups.